Projecting National-Level Prevalence of General Obesity and Abdominal Obesity Among Chinese Adults With Aging Effects - Tian, Xu; Wang, Hui (Frontiers in Endocrinology, 2022)
Abstract Objectives: To explore the impact of population aging on the projected prevalence of obesity among Chinese adults in 2030. Methods: In total, 71450 observations were extracted from the China Health and Nutrition Survey between 1991 and 2015.Population was projected to 2030 using a Bayesian hierarchical modeling method. Two different approaches were adopted to estimate and project the national prevalence of overweight/obesity from 1991 to 2030. One method assumed a constant population at the base year, while the other allowed the age and gender distribution vary in each year. Results: Our projection indicated that approximately two-thirds of Chinese adults would be affected by overweight/ general obesity in 2030, and more than 60% of Chinese adults will suffer from abdominal obesity in 2030. Ignoring population aging led to an underestimation of overweight, general obesity and abdominal obesity for women by 3.81, 0.06, and 3.16 percentage points (pp), and overweight and abdominal obesity among men by 1.67 and 0.53 pp, respectively; but the prevalence of general obesity among men will be overestimated by 2.11 pp. Similar underestimations were detected in the estimation from 1991 to 2015. Conclusions: Estimating and projecting the national prevalence of obesity using a constant population structure at the base line would cause significant underestimation if countries are undergoing rapid population aging.